The Perception of the People of Kuningan Regency Regarding the “Free Nutritious Meals Government Program” Through News in the Mass Media - Maula, Tiara Inayatul; Nurfalah, Farida (PT FORMOSA CENDEKIA GLOBAL, 2026)
The Free Nutritional Meals Program is a public policy aimed at improving the nutrition and quality of human resources for schoolchildren. However, its success is also determined by how the public perceives the program through the mass media. The objectives of this study were: 1) to identify public perceptions of the Free Nutritional Meals Program, 2) to determine public responses to the implementation of the Free Nutritional Meals Program, and 3) to identify the role of the mass media in shaping public perceptions of the Free Nutritional Meals Program. This study used a descriptive qualitative approach, located in Kuningan Regency. Data were collected through in-depth interviews, observation, and documentation with three informants selected using purposive sampling. Data were also supplemented with secondary data in the form of journals, books, and media reports. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation. The results showed that the public generally understood the goals, objectives, and benefits of the Free Nutritional Meals Program through media coverage and provided a positive response, accompanied by a critical and realistic attitude towards its implementation in the field. Mass media plays a crucial role in shaping public perception through the presentation of clear information, the use of visuals, and concrete examples of implementation, thus helping the public interpret programs as relevant policy innovations. This research emphasizes the crucial role of mass communication in shaping public perception of government policies.